2017
DOI: 10.1016/j.tips.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of Tauopathy: Causes, Consequences, and Therapeutic Strategies

Abstract: There are currently no disease-modifying therapies for the treatment of tauopathies, a group of progressive neurodegenerative disorders that are pathologically defined by the presence of tau protein aggregates in the brain. Current challenges for the treatment of tauopathy include the inability to diagnose early and to confidently discriminate between distinct tauopathies in patients, alongside an incomplete understanding of the cellular mechanisms involved in pathogenic tau-induced neuronal death and dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
157
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 113 publications
0
157
1
Order By: Relevance
“…To investigate whether the findings in human AD neurons and transgenic mice translated to human brains with pure tauopathy (i.e., NFT pathology without other protein aggregates such as Aβ), we acquired human brain tissue with histopathologically confirmed progressive supranuclear palsy (PSP; Table 1 for patient characteristics). PSP is an age‐associated tauopathy that clinically manifests as parkinsonism with additional motor abnormalities and cognitive dysfunction (Orr et al, 2017) and is neuropathologically defined by the accumulation of four‐repeat (4R) tau, NFTs, gliosis, and neurodegeneration (Flament, Delacourte, Verny, Hauw, & Javoy‐Agid, 1991). Consistent with the results from transgenic mice, CDKN2A was upregulated in PSP brains ( p  = 0.0415, Figure 4g) and expression correlated with NFT deposition, specifically in the parietal lobe (ANOVA, p  = 0.0008; Kendall's Tau rank correlation, p  = 0.059, Figure 4h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether the findings in human AD neurons and transgenic mice translated to human brains with pure tauopathy (i.e., NFT pathology without other protein aggregates such as Aβ), we acquired human brain tissue with histopathologically confirmed progressive supranuclear palsy (PSP; Table 1 for patient characteristics). PSP is an age‐associated tauopathy that clinically manifests as parkinsonism with additional motor abnormalities and cognitive dysfunction (Orr et al, 2017) and is neuropathologically defined by the accumulation of four‐repeat (4R) tau, NFTs, gliosis, and neurodegeneration (Flament, Delacourte, Verny, Hauw, & Javoy‐Agid, 1991). Consistent with the results from transgenic mice, CDKN2A was upregulated in PSP brains ( p  = 0.0415, Figure 4g) and expression correlated with NFT deposition, specifically in the parietal lobe (ANOVA, p  = 0.0008; Kendall's Tau rank correlation, p  = 0.059, Figure 4h).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of tau protein is the most common pathology among these diseases making tau an appealing molecular target for intervention (Orr, Sullivan, & Frost, 2017). Tau‐containing neurofibrillary tangles (NFTs) closely track with disease severity in human AD (Arriagada, Growdon, Hedley‐Whyte, & Hyman, 1992); however, NFT‐containing neurons are long‐lived and do not induce immediate cell death (de Calignon, Spires‐Jones, Pitstick, Carlson, & Hyman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to AD, numerous pathogenic mutations in MAPT gene have been found in the autosomal dominantly inherited dementia FTDP‐17, proving that Tau pathology alone is sufficient to cause neurodegeneration . There are over 50 identified mutations in MAPT that are responsible for FTDP‐17, and most of them occur in the microtubule binding domain of Tau . It has been demonstrated that mutations in MAPT can stimulate fibrillization of Tau even in the absence of polyanionic inducers .…”
Section: Molecular Bases Of Tau Pathology In Tauopathiesmentioning
confidence: 99%
“…63 There are over 50 identified mutations in MAPT that are responsible for FTDP-17, and most of them occur in the microtubule binding domain of Tau. 63,72 It has been demonstrated that mutations in MAPT can stimulate fibrillization of Tau even in the absence of polyanionic inducers. 73 Some Tau mutants have increased tendencies to aggregate into PHFs.…”
Section: Molecular Bases Of Tau Pathology In Tauopathiesmentioning
confidence: 99%
“…Its conversion into pathogenic form, leads to its aggregation and formation 2 of neurofibrillary tangles (NFTs) which eventually form the basis of the tau pathogenesis [2]. Tau aggregation is driven by a variety of factors including post translation modifications such as phosphorylation, mutations of the MAPT (microtubule associated protein tau) gene, injury of the brain, atypical expression of tau isoforms, and spread from the neighbouring cells [3].…”
Section: Introductionmentioning
confidence: 99%